2019
DOI: 10.1088/1742-6596/1362/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Solar Powered Automatic Pesticide Sprayer for Agriculture

Abstract: An automatic pesticide mixing and water level control of irrigation system powered by solar, using PLC and nrf24l01 module is focussed. The proposed system consist of pesticide mixer which automatically mixes the pesticide and water in particular ratio and the mixer is automatically sprayed to the field on the programmed date with the help of PLC. This system will also be useful in monitoring the soil moisture condition and level of the water in the field via moisture sensors and ultrasonic sensor which is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The final phase is regional, global, and open control loops and IoT [7,8]. Examples Seamless internet of things supply chain management and product life cycle management [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The final phase is regional, global, and open control loops and IoT [7,8]. Examples Seamless internet of things supply chain management and product life cycle management [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional spraying involves direct contact with hazardous pesticides. Farmers become chronically intoxicated while performing activities such as mixing, loading, spraying, and cleaning spray pumps, which can lead to chronic diseases such as skin cancer, respiratory diseases, multiple basal cell carcinomas, and squamous cell carcinomas [6].The farmers feel fatigued, dizzy, or have headaches because of the constant manual spraying [7]. Today's world requires technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research concluded that there was a significant relationship between pesticide-using methods and the health impacts on farmers and workers. In the paper "Design and Implementation of Solar Powered Automatic Pesticide Sprayer for Agriculture" [7], the author develops a pesticide mixer that automatically mixes the pesticide and water in a particular ratio, and the mixer is automatically sprayed onto the field on the programmed date with the help of a PLC. Also, soil moisture conditions and the water level are monitored using moisture sensors and ultrasonic sensors.…”
Section: Literature Reviewmentioning
confidence: 99%